Efficacy of bath vaccination with a live attenuated Vibrio harveyi against vibriosis in Asian seabass fingerling, Lates calcariferaq - Chin, Yong Kit; Al-Saari, Nurhidayu; Mohamed Zulperi, Zarirah; Mohd Aris, Aslizah; Salleh, Annas; Silvaraj, Santha; Mohamad, Aslah; Lee, Jing Yie; Saad, Mohd Zamri; Md Yasin, Ina Salwany (Wiley, 2020)
INA SALWANY BINTI MD YASIN/// MOHD ZAMRI BIN SAAD,ANNAS BIN SALLEH,ZARIRAH BINTI MOHAMED ZULPERI/// Aslizah Mohd Aris,Nurhidayu Al‐saari,Yong Kit Chin,Santha Silvaraj,JingYie Lee,Aslah Mohamad